Whetting disadvantaged adults’ appetite for nutrition education - Pettigrew, Simone; Biagioni, N.; Moore, S.; Pratt, Steve (Cambridge University Press, 2016)
Objective: To identify the features of a nutrition education programme for disadvantaged adults deemed most attractive and useful by participants. Design: A two-year, multi-method, qualitative evaluation of pre and post data collected from programme participants. Data were imported into NVivo10 for coding to facilitate a thematic analysis. Setting: Western Australia. Participants: Individuals attending the Western Australian FOODcents nutrition education programme that is designed to provide knowledge and skills needed to consume a healthy diet on a budget. Focus groups were conducted several weeks after course completion (five groups, forty-seven participants), observations were conducted during FOODcents sessions (thirty-one observation episodes, 237 participants), and open-ended questions were asked in pre–post hard-copy surveys administered in sessions (n 927) and an online survey administered on average six weeks after course completion (n 114). Results: The course attributes that were found to be especially important to participants were: (i) user-friendly, practical information that could be immediately translated to their daily lives; (ii) experiential learning that involved direct contact with food products; and (iii) opportunities for social interaction. These aspects of nutrition education were described as being highly influential in the decision to participate in the course, the application of the information in their subsequent food purchase and preparation activities, and their word-of-mouth communications with others about the course. Conclusions: Incorporating aspects of most importance to participants into nutrition education programme delivery and promotion may increase joining rates, enjoyment, satisfaction with course content and, ultimately, the uptake of recommended behaviours.